Penerapan Evaluasi Sumatif dalam Pembelajaran PAI di SMPN 1 Surakarta - Hadi, Abil Fida Muhammad Qois Al; Listari, Defi Anita; Meilawati, Anisa; Inayati, Nurul Latifatul (Lembaga Yasin AlSys, 2024)
Summative assessment refers to a summary of a student's performance and is intended to be reported at the end of a program of study. Although summative assessments do not have a direct impact on learning, they often influence decisions that can impact student learning. This research uses field research with qualitative methods. This method is used to explain complex phenomena by collecting detailed data. The approach used is phenomenological, namely to understand the experiences of research subjects, phenomena, including behavior, perception, motivation, etc., in the context of certain languages and natural environments. Based on the interview findings, before carrying out a summative evaluation, the class teacher carries out a formative evaluation first on PAI learning in junior high school. After carrying out the formative assessment, the PAI teacher at SMPN 1 Surakarta carried out a summative assessment. Summative assessment occurs when all learning material has been completed or at the end of learning, namely during PTS and PAS. At SMPN 1 Surakarta, the summative assessment questions are in the form of multiple choice, true false, matching and essay. Regarding obstacles, because SMPN 1 Surakarta is a state school, the obstacles faced depend on the average level of student achievement. If students are unable to achieve the KKM, they will be given compensation by processing the funding questions submitted in the hope of being able to achieve an assessment according to the specified KKM. Summative assessment is related to summarizing student achievements, and is directed at reporting at the end of a study program. Summative assessments do not have a direct impact on learning, although they often influence decisions that may have consequences for students learning.